Struktur, Komposisi dan Pertumbuhan Vegetasi pada Lahan Gambut Bekas Terbakar Tahun 2015 Di UPT Laboratorium Alam Hutan Gambut Sebangau: Structure, Composition and Vegetation Growth on Peat Land Used By Fire In 2015 At UPT Natural Laboratory Of Sebangau Peat Forest - Canra P. Lumban Gaol; Wahyudi Wahyudi; Santosa Yulianto (HUTAN TROPIKA, 2022)
This study aims to determine the structure, composition and growth of vegetation on peatlands burned in 2015 in the Natural Laboratory of Peat Forest (LAHG) Sebangau. The benefit of the research is to provide information on the structure, composition and growth of burned peat forest vegetation.Data retrieval using the checkered line method. Determination of the path with the technique of "Stratified Sampling" with a track area of 3 ha.The results of the analysis of the horizontal structure of the stand resemble an inverted J curve. The rehabilitated and non-rehabilitated areas changed the structure to large diameter classes. The vertical structure of the stand forms an inverted J curve although it is less consistent in the mid-height class. The burned area and not rehabilitated the structure changed in the largest diameter class. The rehabilitated burned area underwent changes in the form of improvements in the number and composition of species in the high-middle class due to rehabilitation activities. The highest Important Value Index (INP) in burned areas was (Combretocarpus rotundatus (Miq) at each growth stage, different for unburned areas the highest INP were (Syzygium sp.) seedlings and poles, sapling level (Garcinia bancana) and tree level (Syzygium sp.) Syzygium sp.).The composition of the rehabilitated area consisted of 12 types of seedlings, 8 types of saplings. The area that was not rehabilitated contained 11 types of seedlings, 13 types of saplings, 4 types of poles and 3 types of trees. The unburnt area contained 21 types of seedlings, 28 types of saplings, 26 types of poles and 23 types of trees. Species diversity and species richness in the burned areas are low, while the unburned forest areas are classified as medium and high. The evenness of species in the three forest conditions was high and evenly distributed. The highest vegetation growth in the rehabilitated area on the BFA transect was (Shorea balangeran (Korth.) Burck), while the slowest growth was (Eleocarpus sp.). On the CN transect, the highest vegetation growth was found in (Syzygium sp.) and the lowest growth was (Shorea balangeran (Korth.).